Management of Personnel Competence in the Development of Agricultural Clusters: From Theory to Practice - Qobulova Maxpubaxon Yakibovna (American Journal of Biodiversity, 2026)
This article comprehensively analyzes the modern system of personnel potential management in the development of agro-clusters in Uzbekistan. Based on Presidential decrees, the priority directions for human capital development in the agricultural sector are highlighted.